Providing Puzzle Playing Therapy with Anxiety Children Due to Hospitalization in Children with Diarrhea in Hospital - Anindita, Angie; Yunike; Rehana (International Journal Scientific and Professional, 2022)
Children with diarrhea who are undergoing treatment in hospital (hospitalization) will usually cause anxiety for the child. The role of nurses has a big role in controlling anxiety by reducing anxiety, namely play therapy by coloring pictures. Puzzle play therapy aims to make children happier or used as entertainment while being treated in hospital and can reduce the level of anxiety in children. Method: The design of this case study is descriptive in the form of a case study with a nursing process approach consisting of assessment, nursing diagnosis, planning, evaluation and documentation. The case study subjects were 2 cases of diarrhea with anxiety nursing problems at the Muhammadiyah Palembang Hospital in 2023. Data collection techniques were by observation, interviews and filling in research instruments for 3 days in the treatment room. Results: The results of the case study after implementing anxiety reduction nursing through puzzle playing therapy showed that the results of patient 1 and patient 2 showed that the level of anxiety decreased. What was found was that there was a significant relationship between Anxiety and the provision of puzzle playing therapy to children with Diarrhea. Discussion: Implementation of anxiety reduction nursing through puzzle playing therapy in Diarrhea patients with Anxiety problems can be applied because it is effective in reducing anxiety in children.